Vibration Reduction Analysis of Bearing Seat Damping Structure of Helicopter Main Reducer Casing - Hao Gao; Jianjun Yang; Hua Dai; Dingjun She (Jixie chuandong)
Aiming at the vibration and noise problem of a helicopter main reduction casing，the dynamics simulation analysis of the main reduction transmission system model is performed to solve the dynamic meshing impact force generated by the spiral bevel gear during high-speed transmission. Taking the main reducer as the research object，based on the damping vibration reduction mechanism，the influence of adding foam aluminum damping material to the bearing seat on the vibration of the casing is analyzed. The vibration response of the casing is solved，and the influence of the aluminum foam material of different thicknesses on the natural frequency and modal damping ratio of the casing is studied. The influence of different installation positions of the damping layer on the vibration reduction effect of the damping structure of the bearing seat is analyzed. The calculation results show that the vibration acceleration peak of the casing at the meshing frequency is reduced by 14.89%. Adding damping materials to the bearing seat can increase the modal damping ratio of the casing and effectively suppress the vibration of the casing.